MARKETING RESEARCHES OF MEDICINAL AND COSMETIC REMEDIES INTENDED FOR APPLYING IN VARIOUS FORMS OF ALOPECIA - I. O. Yarema; M. I. Fedorovska; L. V. Sokolova (Zaporozhye State Medical University, 2014)
Pathological hair loss - alopecia - is an urgent problem that takes one of the leading places in the pathology of skin structure. There are different types of alopecia, the most common forms are androgen and telogen (symptomatic) alopecia. Androgenic alopecia (AA) isa progressive alopecia caused by androgens action on hair follicle in patients with hereditary predisposition, which is often manifested not only with excessive hair loss, but also with the appearance of dandruff. Uncontrolled use of cosmetic products for combating hair loss is increased in view of high prevalence among young people, and as advertising in the media. Therefore, an important task of modern pharmacy is to create a medicinal remedy that contribute efficient and controlled correction of AA and provide the pharmaceutical market of Ukraine with available economical means. The significant range of cosmetics and medicinal products to eliminate dandruff and hair loss correctionare implementedin Ukraine pharmacy network today. However, the amount of medicinal remedy decreases every year. Most of them, after re-registration movetothe category of cosmeceuticals.This cause the significant increase in the value. For example, the number of medicinal remedy registered in Ukraine for local and systemic treatment of alopecia compared with 2012 decreased approximately on 36%, and drugs to treat dandruff - 17%. Today the amount of native medicines for the treatment of alopecia and dandruff is limited and is only 23%, compared with foreign firms. Leading positions in the import medicines of this group are occupied by India, Germany and France, and the share of foreign drugs is 77% from the total. Cosmetic hair loss remedies are presented significantly numerous, compared to medicinal remedy, an arsenal of forms production, including shampoos, masks, lotions, oil, balms, solutions for rubbing into the scalp, capsules for internal use and so on. The main components of active cosmeceuticals are plant extracts. After comparative analysis of prices for medicinal and cosmetic remedies, it has been found that the cost is ranged from 15 to 400 UAH. Thus, the expensive niche (200-400 UAH) consists mainly of foreign production cosmeceuticals. Therefore, the range of hair loss medicines in the native market is created mainly by foreign-made drugs,this fact significantly increases their cost. Medicines for alopecia correction and elimination of dandruff are presented in various forms of production, among them shampoos and solution for external use which take dominating position. The composition of symptomatic alopecia drug consists usually of plant extracts, growth activators, local irritant substances, vitamins and microelements. The basic for the AA treatment is drug of local action based on minoxidyl and tablets of finasteride for internal use. These synthetic drugs have a number of drawbacks and side effects. So, given that foreign high-value medicinal remedies from baldness dominate on the pharmaceutical market and the range of medicines is limited, the elaboration and implementation of effective and safe medicines of plant origin in pharmaceutical practice, which would affect the pathogenic mechanisms of this disease, are promising and urgent task.